Reforming the European Parliament: Brexit creates opportunity for more than just seat redistribution - but plans are modest (for now) - Nicolai von Ondarza; Felix Schenuit (Stiftung Wissenschaft und Politik (SWP), 2018)
Reform of the European Parliament is on the agenda in the run-up to the 2019 European elections. Two impulses coincide here: First of all, Brexit requires a decision on whether to redistribute the 73 British seats, and if so how. Secondly, the European Parliament is sitting on a backlog of long-overdue reforms relating to its composition; this latter aspect is unlikely to be resolved before the 2019 elections. The Italian and French governments suggest creating a single EU constituency fought on the basis of transnational lists, to strengthen the European plane of party-political competition. But the European Parliament's rejection of the proposal underlines the lack of majority support for federal initiatives in the EU's year of reforms. Yet the single constituency discussion does offer potential: Leveraging it to reduce the existing discrepancies in required votes per seat would represent a major contribution to strengthening the Union's democratic legitimacy.
Keywords: 320